Club athletics designing clubs for the future - Hannan, P. (IFAC, 2012)
Powerpoint presentation of the author from Australia at the International Festival of Athletics Coaching in Glasgow, 2012 about clubs for the future for athletics - organisation in general and especially in Australia (e. g. little athletics, Athletics Australia, club structure/types of clubs, the role oc coaches...). Questions as "What is the Optimal Sized Club?" or "How many coaches for the `optimal Club`?" are answered.